(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents four new classes of multifunctions called upper contra-(τ_1,τ_2)p-continuous multifunctions, lower contra-(τ_1,τ_2)p-continuous multifunctions, upper almost contra-(τ_1,τ_2)p-continuous multifunctions and lower almost contra-(τ_1,τ_2)p-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper contra-(τ_1,τ_2)p-continuous multifunctions, lower contra-(τ_1,τ_2)p-continuous multifunctions, upper almost contra-(τ_1,τ_2)p-continuous multifunctions and lower almost contra-(τ_1,τ_2)p-continuous multifunctions are established.